2012
DOI: 10.1104/pp.111.191759
|View full text |Cite
|
Sign up to set email alerts
|

Cross Talk among Calcium, Hydrogen Peroxide, and Nitric Oxide and Activation of Gene Expression Involving Calmodulins and Calcium-Dependent Protein Kinases in Ulva compressa Exposed to Copper Excess      

Abstract: To analyze the copper-induced cross talk among calcium, nitric oxide (NO), and hydrogen peroxide (H2O2) and the calcium-dependent activation of gene expression, the marine alga Ulva compressa was treated with the inhibitors of calcium channels, ned-19, ryanodine, and xestospongin C, of chloroplasts and mitochondrial electron transport chains, 3-(3,4-dichlorophenyl)-1,1-dimethylurea and antimycin A, of pyruvate dehydrogenase, moniliformin, of calmodulins, N-(6-aminohexyl)-5-chloro-1-naphtalene sulfonamide, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
108
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(111 citation statements)
references
References 59 publications
3
108
0
Order By: Relevance
“…It has also been reported that the level of H 2 O 2 increases following exposure to elevated temperatures, leading to HSF activation and HSP accumulation in Arabidopsis, tobacco (Nicotiana tabacum), and bacteria (Clostridium acetobutylicum; Volkov et al, 2006;Königshofer et al, 2008;Banti et al, 2010). In contrast, peroxide scavengers and inhibitors of H 2 O 2 generation have been shown to reduce HSP expression in HS-exposed Arabidopsis and tobacco, respectively (Volkov et al, 2006;Königshofer et al, 2008 (Delledonne et al, 1998;Murgia et al, 2004;Zago et al, 2006;Wilkins et al, 2011), antioxidant reactions , heavy metal resistance (González et al, 2012), and adventitious root formation (Bai et al, 2012). Proteomic analysis uncovered cross talk between NO and H 2 O 2 in citrus plants (Tanou et al, 2010).…”
mentioning
confidence: 99%
“…It has also been reported that the level of H 2 O 2 increases following exposure to elevated temperatures, leading to HSF activation and HSP accumulation in Arabidopsis, tobacco (Nicotiana tabacum), and bacteria (Clostridium acetobutylicum; Volkov et al, 2006;Königshofer et al, 2008;Banti et al, 2010). In contrast, peroxide scavengers and inhibitors of H 2 O 2 generation have been shown to reduce HSP expression in HS-exposed Arabidopsis and tobacco, respectively (Volkov et al, 2006;Königshofer et al, 2008 (Delledonne et al, 1998;Murgia et al, 2004;Zago et al, 2006;Wilkins et al, 2011), antioxidant reactions , heavy metal resistance (González et al, 2012), and adventitious root formation (Bai et al, 2012). Proteomic analysis uncovered cross talk between NO and H 2 O 2 in citrus plants (Tanou et al, 2010).…”
mentioning
confidence: 99%
“…Under the action of copper ions on the culture of sea alga Ulva compressa, the rise of the content of nitric oxide, hydrogen peroxide and calcium ions in cells was registered after 2 and 12 hours [8]. Thus the treatment of cells with the NO scavenger levelled the increase of the concentration of endocellular calcium, and the antagonists of calcium removed the rise of NO content.…”
mentioning
confidence: 84%
“…In the alga Ulva compressa, NO is produced in response to high levels of cadmium, leading to Ca 2+ release in the cytosol and activation of calcium-dependent protein kinases (CDPKs) and calmodulins that lead to gene regulation responses. H 2 O 2 is also involved in this event, stimulating both Ca 2+ and NO production (Gonzáles et al 2012). …”
Section: Heavy Metal Stressmentioning
confidence: 97%